Пенсійна реформа в Україні: перспективи проведення другого рівня - В’юшин, А.А. (Культура народов Причерноморья, 2013)
У статті проаналізовано основні демографічні та економічні причини можливого
майбутнього запровадження другого рівня пенсійної реформи в Україні в контексті соціального
реформування держави.
Розглядаються основні тенденції, пов'язані з її введенням, позитивні та негативні економічні та
соціальні наслідки її дії для уряду та населення, аргументована необхідність цього процесу для
подальшого розвитку держави. Описується міжнародний досвід прийняття і дії накопичувальної
системи страхування, виділені основні ризики та перспективи пов’язані з її функціонуванням. В статье проанализированы основные демографические и экономические причины
возможного будущего введения второго уровня пенсионной реформы в Украине в контексте социального
реформирования государства.
Рассматриваются основные тенденции, связанные с её введением, позитивные и негативные
экономические и социальные последствия её действия для правительства и населения, аргументирована
необходимость этого процесса для дальнейшего развития государства. Описывается международный
опыт принятия и действия накопительной системы страхования, выделены основные риски и
перспективы, связанные с её функционированием. Pension reform is one of the main directions in the development of the social system of Ukraine, that
will have a significant impact on the economic and social processes in country. With the introduction of the
accumulative pension insurance system will end the transition from the current solidarity pension system to a
three-tier pension system and change the future of the diversification of sources of income of pensioners in
Ukraine.
In the article has been analyzed prospective second level of the pension reform in Ukraine in the demographic,
economic and social aspects. Considered the basic demographic and economic reasons for the possible future
introduction of the second level pension reform in Ukraine in the context of social reform of the state. Identify
the major factors of future occurrence and operation funded pension system and prove the necessity for the
introduction of this system in Ukraine.
Considered the main trends associated with its introduction, the positive and negative economic and social
consequences of its activities for the government and the public, argued the necessity of this process for the
further development of the state. Describes the international experience of administration and operation of the
funded pension insurance system, identifies the main positive and negative aspects of its of action in the states
identified the most useful elements of action for Ukraine.